ChemInform Abstract: Original Reactivity of α‐Diazo‐β‐Ketoesters Catalyzed by CpRu Complexes. Issue 4 (January 2015) - Tortoreto, Cecilia; Achard, Thierry; Austeri, Martina; Zeghida, Walid; Lacour, Jerome
Abstract Review: 99 refs.